2014
DOI: 10.1103/physrevb.89.134509
|View full text |Cite
|
Sign up to set email alerts
|

Structure and composition of the superconducting phase in alkali iron selenideKyFe1.6+xSe2

Abstract: We use neutron diffraction to study the temperature evolution of the average structure and local lattice distortions in insulating and superconducting potassium iron selenide KyFe1.6+xSe2. In the high temperature paramagnetic state, both materials have a single phase with crystal structure similar to that of the BaFe2As2 family of iron pnictides. While the insulating KyFe1.6+xSe2 forms a √ 5 × √ 5 iron vacancy ordered block antiferromagnetic (AF) structure at low-temperature, the superconducting compounds spon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 40 publications
(58 reference statements)
6
43
0
1
Order By: Relevance
“…The commonly observed 245 phase exists in all the nominal compositions of Rb 0.8 Fe 2 Se 2−z S z as a mesoscopically separated phase. Note that the Fe content is in fact less than 2 which means that all of the samples are in the two phase coexistence region [11][12][13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Rb08fe2s2mentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly observed 245 phase exists in all the nominal compositions of Rb 0.8 Fe 2 Se 2−z S z as a mesoscopically separated phase. Note that the Fe content is in fact less than 2 which means that all of the samples are in the two phase coexistence region [11][12][13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Rb08fe2s2mentioning
confidence: 99%
“…1 (x ≈ 0.8, y ≈ 1.6, referred to as the 245 phase) always seems to be mesoscopically interdigitated with the SC phase that has been suggested to be an iron vacancy free phase in the studies to-date [10][11][12][13][14][15][16][17][18][19][20][21][22][23] . The relationships between the two phases are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…For the superconducting phase, it has been gradually conceived that the main structure is still the same as the typical BaFe 2 As 2 , but both the Fe and K may be deficient, and these deficiencies may form some kind of structures. Recently, the neutron diffraction experiment indicates a potassium deficient but iron stoichiometric formula K x Fe 2 Se 2 for the superconducting phase 21 . Therefore the study of such material is complicated by the nature of mesoscopic phase separation 8,12,13,15,21 , and it is very challenging to explore the properties of the normal state of the superconducting phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the neutron diffraction experiment indicates a potassium deficient but iron stoichiometric formula K x Fe 2 Se 2 for the superconducting phase 21 . Therefore the study of such material is complicated by the nature of mesoscopic phase separation 8,12,13,15,21 , and it is very challenging to explore the properties of the normal state of the superconducting phase. Recently, Yi et al reported the study of ARPES on A x Fe 2−y Se 2 (A = K, Rb) single crystals, and proposed an orbital-selective Mott transition in the normal state 22 .…”
Section: Introductionmentioning
confidence: 99%
“…This entails microscale phase separation, with heterogeneity creating less than 20% of I4/mmm KxFe2Se2, adopting the iron-pnictide ThCr2Si2 superconducting crystal structure, and the majority I4/m K2Fe4Se5 Fe-vacancy-ordered antiferromagnetic phase ( Figure 1) [11,12]. The origin of superconductivity and the precise stoichiometry of iron and potassium content that leads to the superconducting phase are still under debate owing to the intrinsic phase separation and inhomogeneity in this type of chemically complex material [13,14]. Interestingly, the substitution of Se for S in the KxFe2−ySe2−zSz (0 ≤ z ≤ 2) series suppresses the superconducting state (z = 1.6) [15] and eventually the sulphide end-member, KxFe2−yS2, is not superconducting but exhibits a spin-glass behavior at temperatures below 32 K [16].…”
Section: Introductionmentioning
confidence: 99%